2007
DOI: 10.1099/jmm.0.46680-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of real-time PCR and conventional diagnostic methods for the detection of Clostridium difficile-associated diarrhoea in a prospective multicentre study

Abstract: In this prospective multicentre study, an enzyme-linked fluorescent assay (VIDAS CDA2; bioMé rieux), an enzyme-linked assay [Premier Toxins A and B (PTAB); Meridian] and an in-house real-time PCR amplifying the tcdB gene were compared with the cell cytotoxicity assay used as the 'gold standard' for diagnosis of Clostridium difficile-associated diarrhoea (CDAD). Faecal samples from patients with a request for C. difficile diagnosis and samples from patients with diarrhoea hospitalized for at least 72 h were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
4
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 26 publications
2
64
4
2
Order By: Relevance
“…The increase in the number of cases cannot be explained solely by the difference in performance characteristics of the 2 tests: the sensitivity (68%-90% for EIA vs 88%-100% for PCR) and specificity (95.3%-99% for EIA vs 92.6%-98.4% for PCR) of the 2 tests are comparable. [12][13][14]26,27 The sudden increase in the incidence of CDI following the implementation of PCR could be partly explained by the fact that PCR detects toxin genes but cannot determine whether the organism is actively producing toxin. For that reason, some studies concluded that PCR is unreliable in differentiating CDI cases from asymptomatic carriers of a potentially toxigenic organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the number of cases cannot be explained solely by the difference in performance characteristics of the 2 tests: the sensitivity (68%-90% for EIA vs 88%-100% for PCR) and specificity (95.3%-99% for EIA vs 92.6%-98.4% for PCR) of the 2 tests are comparable. [12][13][14]26,27 The sudden increase in the incidence of CDI following the implementation of PCR could be partly explained by the fact that PCR detects toxin genes but cannot determine whether the organism is actively producing toxin. For that reason, some studies concluded that PCR is unreliable in differentiating CDI cases from asymptomatic carriers of a potentially toxigenic organism.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Several studies showed that PCR had an equivalent sensitivity and specificity (up to 100%) compared with toxigenic cultures. [12][13][14] However, PCR may not be useful when trying to differentiate carrier status from true CDI. 15 Moreover, given that clinical manifestations of CDI are milder in children compared with the adult population, 16 and given the current absence of testing strategies that accurately and optimally diagnose CDI, 17 we aimed to determine the proportion of pediatric patients diagnosed as having CDI by PCR who would also be diagnosed by EIA, and to compare the clinical characteristics of PCR + /enzyme-linked immunosorbent assay (ELISA) + vs PCR + /ELISA − patients.…”
mentioning
confidence: 99%
“…All strains were further investigated by PCR ribotyping based upon Bidet et al (2000). Detection of toxin genes was done as described by van den Berg et al (2007).…”
Section: 3mentioning
confidence: 99%
“…Although some studies found that enzyme immunoassay (EIA) compared favorably to cytotoxicity assays (2, 9), several subsequent studies found EIA to have low sensitivity and specificity compared to those of both toxigenic culture and PCR (1,5,11). Also, some concluded that the performance of PCR is superior to that of other available methods (3,7,(10)(11)14). Although commercial FDA-approved assays have been evaluated compared to cytotoxicity assays and culture (4), our study is the first, to our knowledge, to compare two commercially available PCR methods to each other and to a laboratorydeveloped PCR assay with previously published performance characteristics.…”
mentioning
confidence: 99%
“…Several laboratory-developed PCR assays for detection of C. difficile infection (CDI) have been described, and they have demonstrated favorable performances in comparative studies (3,7,10,14). We previously described a real-time PCR assay using a LightCycler (Roche Diagnostics, Indianapolis, IN), which we refer to herein as the LC-CDTX assay (11).…”
mentioning
confidence: 99%